Energy resources and the risk of conflict in shared river basins. (May 2019) - Lee, Sojeong; Mitchell, Sara McLaughlin
This study examines the effect of energy resources on the chances for militarized conflict, water related conflict and cooperation events, and cooperative river treaties between pairs of states on shared international river basins. We examine trade-offs that riparian states can make between energy resources such as oil or natural gas and fresh water resources. Integrating upstream and downstream states' geographical position in a river basin with energy resource information, we examine four related scenarios of states sharing rivers: (1) Joint energy where both upstream and downstream countries have energy resources, (2) Downstream energy where only the downstream state has energy resources, (3) Upstream energy where only an upstream country has energy resources, and (4) No energy . Theoretically, we argue that Downstream energy dyads are most likely to find cooperative solutions to conflicts over shared river resources because downstream states can offer oil and natural gas side payments to upstream states in exchange for greater water supplies. Empirical analyses of dyadic data in shared river basin dyads from 1945 to 2001 provide strong support for the theory. Riparian cooperation through river treaties and diplomacy is best achieved in Downstream energy dyads, where the downstream states have energy resources that can be traded for water resources with upstream states. Militarized conflict and water related conflict events are most likely in Joint energy dyads. Case illustrations from the Aral Sea and Ganges river basins are used to demonstrate the theoretical arguments.